Chemically encoded self-organized quantum chain supracrystals with exceptional charge and ion transport properties. (August 2019) - Hou, Bo; Sohn, Myungbeom; Lee, Young-Woo; Zhang, Jingchao; Sohn, Jung Inn; Kim, Hansu; Cha, SeungNam; Kim, Jong Min
Abstract: Artificially grown superstructures from small building blocks is an intriguing subject in 'bottom-up' molecular science and nanotechnology. Although discrete nanoparticles with different morphologies and physicochemical properties are readily produced, assembly them into higher-order structure amenable to practical applications is still a considerable challenge. This report introduces a stepwise heterogeneous approach for coupling colloidal quantum dots (QDs) synthesis with self-organization to directly generate quantum chains (QCs). By using vulcanized sulfur precursors, QDs are interdigitated into microscale chainlike supracrystals associated with oleylamine and oleic acid as structure directing agents. The cooperative nature of the QD growth and assembly have been extended to fabricate binary (PbS) and ternary metal chalcogenides (CuInS2 ) QC superstructures over a range of length scales. In addition, enhanced ion and charge transfer performance have been demonstrated which are determined to originate from the minimum interparticle distance and nearly bare nanocrystal surface. The process reported here is general and can be readily extended to the production of many other metal chalcogenide QD superstructures for energy storage applications. Graphical abstract: Image 1 Highlights: A new methodology for chemical synthesis self-organized quantum chain supracrystals. Binary and ternary metal chalcogenides quantum chain superstructures have been demonstrated over a range of length scales. Enhanced electrochemical capacity and durability via preserved nanograin boundaries and long-range ordered configuration. Demonstrate exceptional charge and ion transport properties in DFT simulations and lithium-ion batteries.